WAYS OF USING CLOUD SERVICES FOR TRAINING IT BACHELORS - Pavlo Pavlyha (Alfred Nobel University Journal of Pedagogy and Psychology)
The rapid evolution of information technologies (IT) necessitates continuous updates to educational programs to equip future specialists with relevant skills. Integrating modern cloud services into the training process for IT bachelors has become crucial for enhancing practical skills and ensuring graduates are com- petitive in the job market. This article explores the multifaceted application of cloud technologies in IT ed- ucation. The purpose of this study is to outline the ways cloud technologies can be applied in the preparation of IT bachelors across various specializations, compile a list of relevant cloud services, and provide exam- ples of their use in the educational process. The main research tasks are analysing potential methods for in- tegrating cloud services into practical IT training; identifying key practical training areas such as system ad- ministration, DevOps, programming, cybersecurity, data analysis, design, etc.; compiling and systematizing a list of specific cloud services relevant to each identified area; and describing the functionalities and poten- tial usage scenarios of these selected cloud services in laboratory and practical settings. The study employed several research methods, including the analysis of scientific literature, analysis and synthesis, classification, and comparative analysis to achieve its objectives. The research identified core areas for practical IT bachelor’s training: server system administration simulation, DevOps and deployment automation, programming and collaborative development using ver- sion control, virtual labs and simulations, application testing and fault simulation, building and deploy- ing complex infrastructures, practical cybersecurity and ethical hacking, data analysis and business intel- ligence, design and illustration using cloud tools, and other specialized areas like IoT, GIS, blockchain, and game development. For each area, a comprehensive list of relevant cloud services from major providers (AWS, Azure, Google Cloud) and specialized platforms (e.g., AWS EC2, Azure Virtual Machines, Google Com- pute Engine; AWS CloudFormation, Terraform, Jenkins, GitLab CI/CD; AWS Cloud9, GitHub Codespaces, Replit; Cisco Packet Tracer, GNS3, EVE-NG; AWS Fault Injection Simulator, Apache JMeter, Gatling; AWS Elastic Beanstalk, Azure App Service, Kubernetes services like EKS, AKS, GKE; serverless platforms like AWS Lambda, Azure Functions; AWS Security Hub, Metasploit, Kali Linux, OWASP Juice Shop; storage solutions like AWS S3, data warehouses like Redshift and BigQuery, ML platforms like SageMaker and Azure ML, BI tools like Tableau and Power BI; design tools like Adobe Creative Cloud, Figma, Adobe XD, Fusion 360; spe- cialized platforms like AWS IoT Core, ArcGIS Online, Infura, Unity Cloud Build) was compiled and analysed. The study detailed the functional capabilities of these services, encompassing IaaS, PaaS, SaaS, FaaS mod- els, cloud-based IDEs, container orchestration platforms, machine learning environments, data visualiza- tion tools, security management consoles, etc. Potential scenarios for utilizing these services in practical and laboratory classes were described, highlighting how they enable the creation of realistic, scalable, and flexible learning environments. The analysis demonstrates that leveraging cloud services provides students’ access to industry-standard tools and technologies without requiring significant institutional investment in local infrastructure. This approach fosters the development of essential practical competencies required for successful careers in the dynamically changing digital landscape. Conclusions: The active integration of cloud services is identified as an indispensable component of high-quality IT bachelor education. It significantly enhances the practical relevance of the curriculum, align- ing educational outcomes with the demands of the modern labour market and preparing competitive pro- fessionals. The study concludes by emphasizing the importance of cloud adoption in IT training and sug- gests that future research should focus on developing specific methodological recommendations for inte- grating these diverse cloud services into the curricula of various IT specializations.